Simultaneous iron and nickel isotopic analyses of presolar silicon carbide grains. (15th January 2018) - Trappitsch, Reto; Stephan, Thomas; Savina, Michael R.; Davis, Andrew M.; Pellin, Michael J.; Rost, Detlef; Gyngard, Frank; Gallino, Roberto; Bisterzo, Sara; Cristallo, Sergio; Dauphas, Nicolas
Abstract: Aside from recording stellar nucleosynthesis, a few elements in presolar grains can also provide insights into the galactic chemical evolution (GCE) of nuclides. We have studied the carbon, silicon, iron, and nickel isotopic compositions of presolar silicon carbide (SiC) grains from asymptotic giant branch (AGB) stars to better understand GCE. Since only the neutron-rich nuclides in these grains have been heavily influenced by the parent star, the neutron-poor nuclides serve as GCE proxies. Using CHILI, a new resonance ionization mass spectrometry (RIMS) instrument, we measured 74 presolar SiC grains for all iron and nickel isotopes. With the CHARISMA instrument, 13 presolar SiC grains were analyzed for iron isotopes. All grains were also measured by NanoSIMS for their carbon and silicon isotopic compositions. A comparison of the measured neutron-rich isotopes with models for AGB star nucleosynthesis shows that our measurements are consistent with AGB star predictions for low-mass stars between half-solar and solar metallicity. Furthermore, our measurements give an indication on the 22 Ne ( α, n ) 25 Mg reaction rate. In terms of GCE, we find that the GCE-dominated iron and nickel isotope ratios, 54 Fe / 56 Fe and 60 Ni / 58 Ni, correlate with their GCE-dominated counterpart in silicon, 29 Si / 28 Si . The measured GCE trends include the Solar System composition, showing that the Solar System is not a special case. However, as seen in silicon and titanium, many presolar SiC grains are more evolved for iron and nickel than the Solar System. This confirms prior findings and agrees with observations of large stellar samples that a simple age-metallicity relationship for GCE cannot explain the composition of the solar neighborhood.